An Analysis of Chinese Multinationals' Use of Tax Havens - Leotta, Laura (2012)
In this paper it is sought to analyse the use of tax havens by Chinese MNEs. Employing a sample of 100 listed companies – selected amongst China's 1,078 largest firms – , the research focuses on the identification of significant MNEs' characteristics linked to the use of tax havens. Results suggest that among listed companies differences exist between SOEs and private companies' behaviour, distinguishing them in terms of place of incorporation, location of tax-haven affiliates, reported profits (as a percentage) of total revenues, and amount of intra-firm transactions. Sector-wise, the companies seem to follow the same tendency of other traditional MNEs, as firms operating in the services and high-tech sectors are found more prone to the use tax havens. The pervasive employment of affiliates located in low-tax jurisdictions (especially those in dot-tax havens) are considered in line with the overall business strategy pursued by emerging Chinese MNEs, which entails the construction of sustainable comparative advantage based on low costs in order to enlarge their presence at global level leveraging non-traditional factors.